Depression of Bone Density at the Weight-Bearing Joints in Wistar Hannover Rats by a Simulated Mechanical Stress Associated With Partial Gravity Environment - Zhang, Shenke; Ueno, Daishin; Ohira, Takashi; Kato, Hisashi; Izawa, Tetsuya; Yamanouchi, Sakuya; Yoshida, Yukari; Takahashi, Akihisa; Ohira, Yoshinobu (Frontiers in Cell and Developmental Biology, 2021)
The partial gravity environment in space can negatively affect bone health. This survey aimed to study the reaction of different parts of the lower limb bones of rats to partial gravity and the effects of different degrees of gravity on these bony parts. We used 15 8-week-old male Wistar Hannover rats were used at the beginning of the experiment. The degree of mechanical stress was modified, but the ankle joint was maintained at ∼30°, ∼120°, or ∼160° with or without plaster fixation during 10-day hindlimb suspension. Computed tomography was performed to measure the bone parameters [bone mineral density (BMD), trabecular BMD, cortical BMD, and cortical thickness] of each studied group of the whole, proximal, middle, and distal femur and distal tibia. BMD, trabecular BMD, and cortical thickness of the distal femur and proximal tibia of the simulated mechanical stress associated with partial gravity groups were significantly lower than those of the control group; the effect of different degrees of gravity on the same area of hindlimb bone had no significant difference. The simulated mechanical stress associated with partial gravity had the most significant effect on the bone close to the knee joint, with the largest weight-bearing response.